Crystal structure of bulky‐ligand‐protected Au24(S‐C4H9)16. Issue 8 (11th July 2022) - Wijesinghe, Kalpani Hirunika; Oliver, Allen G.; Dass, Amala
Abstract : The Au24 (S‐C4 H9 )16 structure is composed of 13 Au atoms in a cuboctahedral core capped by three Au atoms. This Au16 core is protected by two monomeric staples, two trimeric staples, and four bridging thiolate ligands. Abstract : Atomically precise thiolate‐protected gold nanomolecules have attracted interest due to their distinct electronic and chemical properties. The structure of these nanomolecules is important for understanding their peculiar properties. Here, we report the X‐ray crystal structure of a 24‐atom gold nanomolecule protected by 16 tert ‐butylthiolate ligands. The composition of Au24 (S‐C4 H9 )16 poly[hexadecakis(μ‐ tert ‐butylthiolato)tetracosagold] was confirmed by X‐ray crystallography and electrospray ionization mass spectrometry (ESI–MS). The nanomolecule was synthesized in a one‐phase synthesis and crystallized from a hexane–ethanol layered solution. The X‐ray structure confirms the 16‐atom core protected by two monomeric and two trimeric staples with four bridging ligands. The Au24 (S‐C4 H9 )16 cluster follows the shell‐closing magic number of 8.